2013
DOI: 10.1016/j.jmmm.2013.05.056
|View full text |Cite
|
Sign up to set email alerts
|

High coercivity induced by mechanical milling in cobalt ferrite powders

Abstract: In this work we report a study of the magnetic behavior of ferrimagnetic oxide CoFe 2 O 4 treated by mechanical milling with different grinding balls. The cobalt ferrite nanoparticles were prepared using a simple hydrothermal method and annealed at 500 o C. The non-milled sample presented coercivity of about 1.9 kOe, saturation magnetization of 69.5 emu/g, and a remanence ratio of 0.42. After milling, two samples attained coercivity of 4.2 and 4.1 kOe, and saturation magnetization of 67.0 and 71.4 emu/g respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(35 citation statements)
references
References 23 publications
0
30
3
2
Order By: Relevance
“…The H c value is increased up to x = 0.05 and is then decreased for higher values of 'x', mainly depending upon the size of the crystallite, domain structure and anisotropy of the crystal structure. 51 Initially, the coercive field is increased for x = 0.05 because of the formation of a nanocrystalline structure and the incorporation of Bi 3+ into CoFe 2 O 4 , whereas for x > 0.05, it is minimized due to decrease in anisotropy. This explains how the difficulty of the magnetization direction away from its stable alignment with the preferred axis can be one of the influencing factors for the magnitude of coercivity.…”
Section: Magnetic Studymentioning
confidence: 99%
“…The H c value is increased up to x = 0.05 and is then decreased for higher values of 'x', mainly depending upon the size of the crystallite, domain structure and anisotropy of the crystal structure. 51 Initially, the coercive field is increased for x = 0.05 because of the formation of a nanocrystalline structure and the incorporation of Bi 3+ into CoFe 2 O 4 , whereas for x > 0.05, it is minimized due to decrease in anisotropy. This explains how the difficulty of the magnetization direction away from its stable alignment with the preferred axis can be one of the influencing factors for the magnitude of coercivity.…”
Section: Magnetic Studymentioning
confidence: 99%
“…In Zn-ferrite thin film also, it is possible to get high magnetization and a very low ferromagnetic resonance line width depending on the grain size and their distribution without going through high temperature processing [19,27]. Co-ferrite nanoparticles also show some interesting features like super-paramagnetism [28], increased/decreased saturation magnetization [29,30], low/high coercivity [31,32], and spin glasses [29] depending on the grain size. Song et al [28] observed that Co-ferrite nanocrystals show superparamgnetic behaviour at 300 K and ferrimagnetic behavior at 5 K. They have 3 also observed coercivity (H C ) of 10.8 kOe at 5 K in 5nm Co-ferrite nanocrystals.…”
Section: Introductionmentioning
confidence: 99%
“…Кобальтові ферити володіють великою константою магнітострикції [5][6][7], тому їх часто використовують як феромагнітну складову в композиційних магнітоелектриках [8][9][10]. В останнi роки одним з провiдних напрямiв сучасного матерiалознавства є синтез рiзних речовин з частинками нанометрового розмiру i з заданими властивостями [11].…”
Section: вступunclassified